Dried umbilical cord is a potential material for retrospective diagnosis of intrauterine enterovirus infection. (November 2014) - Morioka, Ichiro; Matsumoto, Masaaki; Miwa, Akihiro; Yokota, Tomoyuki; Matsuo, Kiyomi; Koda, Tsubasa; Nagasaka, Miwako; Shibata, Akio; Fujita, Kaori; Yamane, Masayuki; Yamada, Hideto; Enomoto, Miki; et al.
Abstract Objective: To determine whether dried umbilical cords (UCs) are useful for retrospective diagnosis of intrauterine enterovirus (EV) infection. Methods: Dried UCs in two patients with neonatal EV sepsis and 10 neonates without infectious signs were enrolled. Viral RNA was extracted from their dried UCs, and nested reverse transcription polymerase chain reaction (RT-PCR) was performed. Results: Infection routes estimated by the clinical course were intrauterine infection in Case 1 and post-natal horizontal infection in Case 2. EV-RNA was detected from dried UC in Case 1, but not in Case 2 and 10 neonates. Conclusions: This report showed the potential use of dried UCs for retrospective diagnosis of intrauterine EV infection.